The Principle of Individualization Is as A Key Factor in Teaching and Learning Language - Abdiraupova Dirabo Asror qizi; Ismailov Anvar Rustamovich (Genius Journals, 2021)
Individualization of education is a topic of current interest. With the use of the learning adaptive tools, the individualization of education could become very effective as this form of education could be adapted to the student’s personal characteristics.
Keywords: Individualization; ITC; cognitive; effectively